Contribution of acetic acid to the hydrolysis of lignocellulosic biomass under abiotic conditions. (June 2015) - Trzcinski, Antoine P.; Stuckey, David C.
Highlights: Significant chemical hydrolysis of MSW by acetic acid can take place. Under reduced conditions a maximum solubilization yield of 32% was obtained. Acetic acid chemically hydrolyzes MSW by increasing the pore width. Abstract: Acetic acid was used in abiotic experiments to adjust the solution pH and investigate its influence on the chemical hydrolysis of the Organic Fraction of Municipal Solid Waste (OFMSW). Soluble chemical oxygen demand (SCOD) was used to measure the hydrolysis under oxidative conditions (positive oxidation–reduction potential values), and pH 4 allowed for 20% (±2%) of the COD added to be solubilized, whereas only 12% (±1%) was solubilized at pH7. Under reducing conditions (negative oxidation–reduction potential values) and pH 4, 32.3% (±3%) of the OFMSW was solubilized which shows that acidogenesis at pH 4 during the anaerobic digestion of solid waste can result in chemical hydrolysis. In comparison, bacterial hydrolysis resulted in 54% (±6%) solubilization.